SETTLEMENT IN THE NOTHERN PART OF BEKASI REGENCY, WEST JAVA PROVINCE, BASED ON CONE PENETRATION TEST DATA - Jatsiah, Siti Nadia; Ismawan, Ismawan; Khoirullah, Nur; Pramudyo, Tulus (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
In the nothern part of Bekasi Regency, the soil layers are dominated with alluvial deposit, especially clay and silt deposit. It makes the potential of the settlement in this area is getting higher. In this research, Cone Penetration Test (CPT) have been done to determine the soil layers from the surface till the 20 meters depth and to identify other soil properties, such as unit weight, compression index, swelling index, void ratio, etc. This research aims to analyze the total settlement in the northern part of Bekasi Regency based on CPT data. The total settlement is calculated by using the theory of One-Dimensional Primary Consolidation based on CPT data. The research area shows that the highest result of total settlement calculation is in the northern part of research area which directly adjacent to the Java Sea. It can be happened because the clay layers in northern part is way thicker than the other area.